2014
DOI: 10.5585/remark.v13i5.2781
|View full text |Cite
|
Sign up to set email alerts
|

Atributos de Estilo de Vida do Consumidor Relacionados ao Consumo de Produtos Orgânicos no Varejo Especializado

Abstract: Com o objetivo de avaliar a relao entre os atributos de estilo de vida e o consumo de produtos orgnicos no varejo especializado, a presente pesquisa procurou entender quem o consumidor de produtos orgnicos no varejo especializado. Para atender a este objetivo, foi realizada uma pesquisa de campo com natureza qualitativa e quantitativa junto a uma amostra de 60 indivduos abordados no momento da compra em um supermercado especializado em produtos orgnicos na cidade de So Paulo/SP. Como resultado foi observado q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
4
0
4
Order By: Relevance
“…The latter wording appears in the first version of the scale in Spanish (Sánchez García et al , 1998). Likewise, with respect to item IT5, which uses the comparison “are worse than the conventional ones”, Braga Junior et al (2014) replaced the term “conventional” with “traditional”, implying that the two terms are synonyms. In reality, however, these terms may have a different or even opposite meaning (Gliessman, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter wording appears in the first version of the scale in Spanish (Sánchez García et al , 1998). Likewise, with respect to item IT5, which uses the comparison “are worse than the conventional ones”, Braga Junior et al (2014) replaced the term “conventional” with “traditional”, implying that the two terms are synonyms. In reality, however, these terms may have a different or even opposite meaning (Gliessman, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of this scale, no study has been identified that explicitly addresses this issue. However, several scholars (Chen, 2007; Braga Junior et al , 2014; Rojas–Méndez et al , 2015) have reported reliability scores that are greater than 0.70. These findings suggest that the scale is reflective because calculating reliability or convergent validity when using a formative approach does not make sense (Coltman et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors developed a scale with nine items scored on a 7-point scale ranging from 1 (totally disagree) to 7 (totally agree). Several studies [86,87] have reported its reliability (Cronbach's alpha > 0.85) and convergent and discriminant validity. This measurement is only focused on organic food, and it does not introduce any comparison with conventional food.…”
Section: Explicit Attitudes Toward Organic Food (Pro)mentioning
confidence: 99%
“…Moraes, Braga Júnior y Lourenzani (2015), establecen que el consumidor contemporáneo ha establecido una serie de requisitos éticos hacia las empresas, a través de los cuales puede determinar lo que está bien y lo que está mal de acuerdo con su cultura, su estrato económico y nivel social (Braga Júnior, Veiga Neto & Moraes, 2014). Así se tiene una nueva perspectiva de consumo en la que las decisiones de compra establecen conexiones fuertes con la sostenibilidad, orientadas por aspectos ambientales, sociales y económicos (Moraes et al, 2015), y guiadas además por la tecnología, con la cual se genera un consumidor más informado y complejo en sus demandas (Kotler, Kartajaya y Setiawan, 2010).…”
Section: Fundamentación Teórica: El Turismo Sostenible Visto Como Un unclassified